Higher ultra-processed food consumption is associated with poor lipid profile in adolescents - Sandra Abreu; Margarida Liz Martins; Sofia Rodrigues; Carla Moreira; Luís Lopes; César Agostinis-Sobrinho; Eduarda Sousa-Sá; Rute Santos (Food and Humanity, 2026)

High virulence of Cordyceps javanica to eggs and all nymphal stages of cashew whitefly Aleurodicus cocois in a screenhouse - Pedro Vitor Moura Silva; Nivia da Silva Dias; Sandra Maria Morais Rodrigues; Marcela Camily Rodrigues Gomes; Gabriela Priscila Sousa Maciel; Heloiza Alves Boaventura; Jose Francisco Arruda e Silva; Celli Rodrigues Muniz; Eliane Dias Quintela (Crop Protection, 2026)

Effects of garlic and rosemary essential oils on growth performance, carcass traits, and meat quality of lambs fed high-concentrate diets - Elias Rodrigues Cavalheiro Junior; Wellington Felipe Caetano; Kawane Dias da Silva; Erica Regina Rodrigues; Guilherme Agostinis Ferreira; Angela Rocio Poveda Parra; Ivone Yurika Mizubuti; Sandra Maria Simonelli; Rodolpho Martin Do Prado; Odimári Pricila Prado Calixto (Small Ruminant Research, 2026)

CBD-rich oil nanoemulsion mitigates long-term testicular and endocrine toxicity induced by prenatal valproic acid exposure in rats - Mariana de França Oliveira da Silva; Fernanda Carolina Ribeiro Dias; Amanda Rodrigues dos Santos Magnabosco; Cláudia Kathariny da Silva Farias; Sandra Maria de Torres; Antônio José Alves; Pabyton Gonçalves Cadena; Valdemiro Amaro da Silva Júnior (Reproductive Toxicology, 2026)

Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

DNA barcoding uncovers two putative new species in Trachelyopterus (Siluriformes: Auchenipteridae) - Fiorindo José Cerqueira; Maelin da Silva; Chrystian Aparecido Grillo Haerter; Sandra Mariotto; Liano Centofante; Eliana Feldberg; Orlando Moreira Filho; Vladimir Pavan Margarido; Daniel Rodrigues Blanco; Roberto Laridondo Lui (Journal of Fish Biology, 2026)
Trachelyopterus is a cryptic genus within the Neotropical catfish family Auchenipteridae with a complex history of taxonomic revisions. Despite the notable morphological and genetic similarities among its species, some studies suggest that the genus harbours greater diversity than is currently recognized, including additional species yet to be formally described. One of the most widely used and effective approaches for investigating species delimitation and assessing biodiversity is DNA barcoding. The application of DNA barcoding has expanded considerably over the past decade, contributing significantly to the understanding of diversity across numerous groups of Neotropical fishes. Thus, in this study, we employed the DNA barcoding approach in both phenetic and phylogenetic contexts to investigate species diversity within the genus Trachelyopterus . Our sampling included four valid species previously identified based on morphology, collected from six hydrographic basins across the Neotropical region: Trachelyopterus galeatus , Trachelyopterus striatulus , Trachelyopterus porosus and Trachelyopterus coriaceus. Our results corroborate the validity of these four species and reveal two distinct lineages: one from the Araguaia River basin and another from the Pantanal in the Paraguay River basin, both of which may represent previously unrecognized species.

Digoxin Derivative BD-8 Attenuates Oxidative Stress and Neuroinflammation in an LPS-Induced Experimental Model - Vitória Karolina Brandão Souza; Davi Azevedo Ferreira; Antônio Pereira Ribeiro Arantes; Elton de Sá Figueiredo; Millena Ferreira Rodrigues Fonseca; Pâmela Yasmin de Oliveira Ferreira; Martina Raissa Ribeiro; Paulo César Ghedini; Andreza Amália de Freitas Ribeiro; José Augusto Ferreira Perez Villar; Maira de Castro Lima; Israel José Pereira Garcia; et al. (Cell Biochemistry and Biophysics, 2026)
Chronic neuroinflammation contributes to neuronal damage through oxidative stress and inflammatory mediators, highlighting the need for novel therapeutic strategies. This study evaluated the cytotoxicity and neuroprotective effects of BD-8, a digoxin-derived cardiosteroid, in vitro and in vivo. BD-8 showed lower cytotoxicity than digoxin, with CC₅₀ values of 7.4 µM in SH-SY5Y cells and 8.5 µM in BV-2 cells, while digoxin presented a CC₅₀ of 33 nM in SH-SY5Y cells. In vivo, BD-8 did not alter cardiac, hepatic, or renal biochemical markers, supporting its systemic safety profile. In the open-field test, BD-8 prevented LPS-induced locomotor impairment, significantly increasing total crossings at 0.56 mg/kg (62.07 ± 3.269; P < 0.05) and 1.12 mg/kg (66.31 ± 5.282; P < 0.001) compared to the LPS group. BD-8 also reduced lipid peroxidation levels in the cortex at 0.56 mg/kg (14.38 ± 0.5568; P < 0.001) and 1.12 mg/kg (13.94 ± 0.8372; P < 0.001), and in the hippocampus at 1.12 mg/kg (14.04 ± 0.5223; P < 0.001). Additionally, BD-8 modulated antioxidant enzyme activities, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), in both the cortex and hippocampus and reduced IL-6 levels in these brain regions without altering BDNF (Brain Derived Neurotrophic Factor) levels. These findings support BD-8 as a promising candidate for neuroinflammatory disorders.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Microscale sealed vessel (MSSV) technique in petroleum systems: a review - Sandra B. Jorge; André L.S. Pestilho; Juliana M. Sousa; Antônia M. Corrêa; Hemmely G. de S. Severino; Alice Maria S. Rodrigues; Kátia Z. Leal; Cleverson J.F. de Oliveira; Daniel S. Dubois; Marcelo C. Bernardes (Organic Geochemistry, 2026)

The impact of Paullinia cupana extract on pharmacokinetics of phenytoin in rats - Eunice Alves; Sandra Ventura; Sara Meirinho; André R.T.S Araujo; Amílcar Falcão; Márcio Rodrigues; Gilberto Alves (Natural Product Research, 2026)

Lung deposition, health risks, and composition of PM2.5 collected in an industrial area in Southern Brazil - Camila N. Farias; Gabriel D. Barp; Eduardo Karnopp; Katarina O. Rodrigues; Marcos A. Hortellani; Jéssica C. Santos-Silva; Jorge E.S. Sarkis; Mariane Bonatti-Chaves; Sandra H.W. Medeiros; Pérola C. Vasconcellos (Atmospheric Pollution Research, 2026)

Integration of Multi-Omics Data To Understand the Multifaceted Role of RAMP1 across Different Cancer Types - Gabrielle da Costa Cabral; Letícia Almeida Rodrigues; Júlia de Almeida Cabral Candiago; João Felipe Fernandes Ferreira Procópio; Júlia Costa Cerqueira Silva; Maria Eduarda Barbosa de Lima; Ana Stella Gisela Ellery Costa Lima; José Valmir Falcão da Costa Júnior; David Abner Santos de Araújo; João Paulo Emiliano da Silva; Sofia Amancio de Almeida Oliveira; Rafael de Oliveira Calaça Farias; et al. (Cell Biochemistry and Biophysics, 2026)
Receptor Activity-Modifying Protein 1 (RAMP1) is a Calcitonin Receptor-Like Receptor (CALCRL)-associated protein with significant relevance in oncogenesis and tumor progression. It acts as a context-dependent allosteric modulator of GPCRs. This integrative review synthesizes evidence from multiple omics layers—transcriptomics, proteomics, epigenomics, and pan-cancer datasets—to clarify the role of RAMP1, its signaling pathways, and its relationship with the tumor microenvironment. Multi-omics integration highlighted several key findings: transcriptomic and regulatory signatures frequently associate RAMP1 overexpression with epithelial–mesenchymal transition; RAMP1 is associated with the coordinated activation of GPCR-dependent pro-tumorigenic pathways; and the CGRP/RAMP1 axis is associated with CD8 + T-cell exhaustion and potential resistance to immune checkpoint inhibitors. Pan-cancer analyses revealed marked expression heterogeneity. RAMP1 is strongly overexpressed in hepatocellular carcinoma (LIHC) and downregulated in kidney renal clear cell carcinoma (KIRC), reinforcing the importance of context-specific interpretation. It also emerges as an unfavorable prognostic biomarker in osteosarcoma, rectal adenocarcinoma, prostate cancer, and Ewing sarcoma, suggesting its potential value as a strategic therapeutic target. Future studies should prioritize spatial transcriptomics and the pharmacological modulation of the CGRP/RAMP1 axis to refine precision oncology strategies.

Brazil’s climate leadership paradox: hosting COP30 amid domestic environmental rollbacks - Daniela Debone; Ronan Adler Tavella; Mariana Vieira da Costa; Eliane Seiko Maffi Yamada; Flavio Manoel Rodrigues da Silva Júnior; Sandra de Souza Hacon; Paulo Artaxo; Simone Georges El Khouri Miraglia (International Environmental Agreements: Politics, Law and Economics, 2026)

Neuroinflammation and RAMP1: the Role of the Peripheral and Central Nervous System in Tumor Progression - Pedro Daniel Moumesso Cavalcante; Jonas Lucas Dias da Silva; Laryssa Rosy Santos Oliveira; Rikelly Barbosa da Silva; Juliana Acioli Costa Lima; Guilherme de Brito Souza; Davi Ramon da Silva Santos; Júllia Victória Nascimento de Abrantes; Mateus Lima de Farias; Sofia Amancio de Almeida Oliveira; João Paulo Emiliano da Silva; Rafael de Oliveira Calaça Farias; et al. (Cell Biochemistry and Biophysics, 2026)
Calcitonin gene-related peptide (CGRP) and receptor activity modifier protein 1 (RAMP1) form a critical neuroimmunoendocrine axis in the modulation of neuroinflammation, pain, and tumor progression. CGRP, released by sensory and sympathetic fibers, is a potent vasodilator and nociceptive modulator; its action depends on the receptor composed of CALCRL and RAMP1. In the central nervous system, the activation of microglia and astrocytes and the induction of pathways such as NF-κB and MAPK culminate in the production of proinflammatory cytokines (TNF-α, IL-6), differing from systemic inflammation due to the presence of the blood-brain barrier and the glial microenvironment. Preclinical evidence demonstrates RAMP1 expression in neurons, glial cells, endothelium, and macrophages; CGRP/RAMP1 signaling promotes vascular permeability, cytokine release, and angiogenesis, potentially synergizing with VEGF. In animal models and cell cultures, genetic or pharmacological manipulations of the axis reduce tumor angiogenesis, pro-tumor immune infiltration, tumor growth, and nociceptive behavior. Given the clinical availability of CGRP antagonists and monoclonal antibodies, blocking the CGRP/RAMP1 axis is a promising translational strategy for modulating tumor progression and cancer pain. This review summarizes preclinical evidence on mechanisms and therapeutic feasibility. The article includes preclinical and clinical safety and biomarker studies.

Sex-dependent therapeutic effects of nano-curcumin on alzheimer’s disease: enhanced cognitive and physiological restoration in female mice - Karline da Costa Rodrigues; Meliza da Conceição Oliveira; Isadora Cielo de Souza; Andreza Wachholz Igansi; Ana Vitória Barbosa Lopes; Camila de Oliveira Pacheco; Sandra Elisa Hass; Ricardo Frederico Schumacher; Cristiane Luchese (Psychopharmacology, 2025)

Chemical profile, cytoprotection study and anxiolytic potential of Lentinus edodes extracts - Matheus da Silva Campelo; Elison Breno de Alencar Dantas; Vitória Maria de Freitas Franco; Izabell Maria Martins Teixeira; Hilton César Rodrigues Magalhães; Guilherme Julião Zocolo; Sandra de Aguiar Soares; Alice Maria Costa Martins; Tiago Lima Sampaio; José Eduardo Ribeiro Honório Júnior; Maria Elenir Nobre Pinho Ribeiro (Food Research International, 2025)

Direct U–Pb dating of vitrinite in coal - Beilei Sun; Yuexing Feng; Sandra Rodrigues; Charlotte M. Allen; Joan S. Esterle (Chemical Geology, 2025)

Are fish larvae contaminated before they start eating? First evidence of microplastic contamination in the yolk-sac of wild fish larvae - Sabrina M. Rodrigues; Francisca Espincho; Michael Elliott; C. Marisa R. Almeida; Sandra Ramos (Frontiers in Marine Science, 2025)
Microplastics (MPs) ingestion in wild fish during the early stages remains a field with scarce information and contradictory findings in laboratory studies. This study evaluated whether MPs contamination of larval fish stages begins at the commencement of the exogenous feeding phase and whether different species and ontogenetic development stages exhibit different profiles of MPs contamination. We assessed, for the first time, the presence of MPs in the larval stages of two species: the European sardine ( Sardina pilchardus ), a marine migrant species, and the common goby ( Pomatoschistus microps) , an estuarine resident species, inhabiting the Douro Estuary (NW Portugal). In both species, MPs were found even in the yolk-sac stage, when fish larvae still have endogenous feeding and do not actively prey on other organisms. This illustrates that fish larvae are already contaminated at a stage where the mouth is still not fully open, further indicating that MPs were not actively ingested. MPs contamination did not vary between species or throughout the ontogenetic development stages, showing similar levels of contamination and MPs contamination profiles. This novel study provides relevant insights into MPs contamination processes, showing that MPs contamination can occur early in the life cycle of fishes, from hatching onwards. Furthermore, the presence of MPs in fish larvae appears to be more dependent on the MPs that are in higher abundance in the surrounding water than fish larvae preferences or ecological guild, physical characteristics, or even the ontogenetic developmental stage.

Physical Interactions between Cancer Cells and Tumor Microenvironment - Andressa Beatriz Apolinário da Silva Correia; Beatriz Medeiros de Souza Melo; Bruna Alves da Silva; Giovana Cruz Maciel; Guilherme Matheus Santos Marques Cavalcante; João Pedro Almeida dos Santos; Layza Maria Barbosa Silva; Luís Filipe Pereira Rocha; Maria Beatriz Cavalcante Brêda; Maria Eduarda Teixeira de Oliveira; Kayo Felipe Barbosa Lima; Luiz Ben-Hur de Oliveira Wanderley Nepomuceno; et al. (Cell Biochemistry and Biophysics, 2025)

Biostimulation with rams improved embryo quality without modifying the ovulatory response in superovulated ewes - Ana Paula Pereira Schmidt; Felipe Zandonadi Brandão; Juliana Dantas Rodrigues Santos; Camila Correa Roza Laeber; Sandra Ribeiro da Silva; Nathália Dutra Knust; Ribrio Ivan Tavares Pereira Batista; Maria Emília Franco Oliveira; Joanna Maria G. Souza-Fabjan; Mário Felipe Alvarez Balaro; Jeferson Ferreira da Fonseca; Rodolfo Ungerfeld (Theriogenology, 2025)

Marshallius anacardii Lima, 1979 (Coleoptera: Curculionidae): a hidden enemy for Brazilian cashew production - Wenner Vinicius Araújo Saraiva; Lincon Matheus Araujo Silva; Gabriela Priscila de Sousa Maciel; Poliana Martins Duarte; Ester Azevedo do Amaral; Nívia da Silva Dias-Pini; Ariane Morgana Leal Soares; Eduardo Pereira de Sousa Neto; Jakeline Maria dos Santos; Sandra Maria Morais Rodrigues; Francisco das Chagas Vidal Neto (Phytoparasitica, 2025)

Li concentration and isotopes in kaolinite and organic of coals determined by secondary ion mass spectrometry - Jia Song; Beilei Sun; Sandra Rodrigues; Chao Liu; Zhanming Guo; David French (International Journal of Coal Geology, 2025)

Comparative analysis of two immunosuppression protocols for vulvovaginal candidiasis induction in Wistar rats - Félix Roman Munieweg; Thais Pinheiro Ribeiro; Jean Ramos Boldori; Nathane Rosa Rodrigues; Nicolle Lauay Carvalho Sanches Hoesel; Ana Luiza Reetz Polleto; Cheila Denise Ottonelli Stopiglia; Sandra Elisa Haas; Cristiane Casagrande Denardin (Brazilian Journal of Microbiology, 2025)

Anatomical traits of epicarp and pericarp in Eugenia involucrata and Eugenia pyriformis: potential implications for postharvest behavior - Marcelo Almeida de Oliveira Junior; Bruna do Amaral Brogio Colli; Liliane Cristina Libório Stipp; Sandra Maria Carmello-Guerreiro; Simone Rodrigues da Silva; Francisco de Assis Alves Mourão Filho (Brazilian Journal of Botany, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

First evaluation of the efficacy and operational cost of acaricidal bath combining different droplet sizes, pressures and spray patterns in dairy cows naturally infested with Rhipicephalus microplus - Gabriel Resende Souza; Beatriz Rezende Gandra de Araújo; Sandra Gesteira Coelho; Ricardo Nascimento Araújo; Welber Daniel Zanetti Lopes; Daniel Sobreira Rodrigues; Lorena Lopes Ferreira (Tropical Animal Health and Production, 2025)

Ursolic acid derivatives improved clinical signs of experimental autoimmune encephalomyelitis by modulating central nervous system inflammation - Elaine Carlos Scherrer; Karla Antunes Ramos; Ydia Mariele Valadares; Igor Gabriel Machado Soares; Alessandra Paula Carli; Fernando Sá Silva; Jeferson Gomes Silva; Daniel Gomes Alvarenga; Alessa Sin Singer Brugiolo; Rodrigo Moreira Verly; Maiara Rodrigues Salvador; Angelo Marcio Leite Denadai; et al. (Metabolic Brain Disease, 2025)

Brazilian Green Propolis Extract-Loaded Poly(Ε-Caprolactone) Nanoparticles Coated with Hyaluronic Acid: Antifungal Activity in a Murine Model of Vulvovaginal Candidiasis - Aniely Dos Reis Teixeira; Amanda De Vasconcelos Quaresma; Renata Tupinambá Branquinho; Patrícia Capelari De Oliveira; Jorge Andrés García Suárez; Geraldo Célio Brandão; Ana Paula Moreira Barboza; Marcelo Gonzaga De Freitas Araújo; Juliana Teixeira De Magalhães; Sandra Aparecida Lima De Moura; Gisele Rodrigues Da Silva (AAPS PharmSciTech, 2025)

The roles of periostin derived from cancer-associated fibroblasts in tumor progression and treatment response - Yasmin De Oliveira Macena; Maria Eduarda Nunes Cezar; Cinthya Brunelly Ferreira Lira; Laryssa Bheatriz Dantas Machado De Oliveira; Thais Noronha Almeida; Ana Dora Alecio Virtuoso Costa; Bernardo Mansur Dantas De Araujo; Durval de Almeida Junior; Henrique Macêdo Dantas; Emanuel Cézar De Mélo; Sandra Taveiros de Araújo; Raimundo Rodrigues de França Júnior; et al. (Cancer and Metastasis Reviews, 2025)

Effect of torrefaction severity on the energy recovery from amazonian wood residues for decentralized energy conversion systems - Edgar A. Silveira; Giulia Cruz Lamas; Pedro Paulo de O. Rodrigues; Normando P.B. Souto; Bruno Sant’Anna Chaves; Luiz Gustavo Oliveira Galvão; Lucélia A. Macedo; Juliana Sabino Rodrigues; Sandra M. Luz; Patrick Rousset; Thiago de Paula Protásio (Biomass and Bioenergy, 2025)

Treatment of mycotic rhinitis caused by aspergillus fumigatus in a quarter horse mare using topical clotrimazole and oral potassium iodide - Juliana de Moura Alonso; Marcos Jun Watanabe; Sandra de Moraes Gimenes Bosco; Emanuel Vitor Pereira Apolonio; Artur Bibiano de Vasconcelos; Ana Carolina do Prado; Ana Liz Garcia Alves; Celso Antonio Rodrigues; Carlos Alberto Hussni (Veterinary Research Communications, 2025)

Mechanisms and effects of AdipoRon, an adiponectin receptor agonist, on ovarian granulosa cells—a systematic review - Lucas Fornari Laurindo; Lívia Fornari Laurindo; Victória Dogani Rodrigues; Eduardo Federighi Baisi Chagas; Jéssica da Silva Camarinha Oliveira; Virgínia Maria Cavallari Strozze Catharin; Sandra Maria Barbalho (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring the benefits of astaxanthin as a functional food ingredient: Its effects on oxidative stress and reproductive outcomes in women with PCOS – A systematic review and single-arm meta-analysis of randomized clinical trials - Victória Dogani Rodrigues; Beatriz Leme Boaro; Lívia Fornari Laurindo; Eduardo Federighi Baisi Chagas; Enzo Pereira de Lima; Lucas Fornari Laurindo; Sandra Maria Barbalho (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unraveling the rationale and conducting a comprehensive assessment of AdipoRon (adiponectin receptor agonist) as a candidate drug for diabetic nephropathy and cardiomyopathy prevention and intervention—a systematic review - Lucas Fornari Laurindo; Lívia Fornari Laurindo; Victória Dogani Rodrigues; Virgínia Maria Cavallari Strozze Catharin; Otávio Augusto Garcia Simili; Gabriella Oliveira Barboza; Vitor Cavallari Strozze Catharin; Kátia Portero Sloan; Sandra Maria Barbalho (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Assessing interactions between antibiotics and triazine porous organic polymeric sorbents by photophysics - Pedro M.C. Matias; Ana Clara B. Rodrigues; Sandra C.C. Nunes; Alberto A.C. Canelas Pais; Dina Murtinho; Artur J.M. Valente (Environmental Pollution, 2024)

History matters: evolutionary and demographic reconstruction of the Southwest Atlantic loggerheads (Testudinata: Cheloniidae) - Sandra Ludwig; Laís Amorim; Alberty Xavier; Paula Rodrigues Guimarães; Sarah Maria Vargas (Evolutionary Ecology, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

System fertilization in integrated crop-livestock management favors microbial processes, soil quality and production profitability - Davi Santos Tavares; Aline de Jesus Franco; Jessyca Adriana Gomes Florêncio da Silva; Tamires Rodrigues dos Reis; Maria Clara Soares; Layane Aparecida Mendes dos Santos; Gabriela Castro Pires; Sandra Maria Monteiro de Araújo Souza; Luiz Guilherme Santos de Oliveira; Aline Oliveira Silva; Leandro Pereira Pacheco; Edicarlos Damacena de Souza; et al. (Agriculture, Ecosystems & Environment, 2024)

Açai seed biochar improves soil quality and black pepper seedling development in the Amazon region - Moises de Souza Mendonça; Wanderley José de Melo; Gabriel Maurício Peruca de Melo; Liandra Maria Abaker Bertipaglia; Ademir Sergio Ferreira Araujo; Iolanda Maria Soares Reis; Sandra Mara Barbosa Rocha; Thiago Assis Rodrigues Nogueira; Cassio Hamilton Abreu-Junior; Arun Dilipkumar Jani (Journal of Environmental Management, 2024)

Waste-to-energy in the civil-construction sector toward the valuation of wood construction residues: Integration of torrefaction process - Thais Barbosa; Bruno Sant’Anna Chaves; Luiz Gustavo O. Galvão; Giulia Cruz Lamas; Pedro Paulo de Oliveira Rodrigues; Mayara Gabi Moreira; Thiago de Paula Protásio; Sandra M. Luz; Juliana Sabino Rodrigues; Edgar A. Silveira (Fuel, 2024)

A new perennial forage module coupled with the ECOSMOS terrestrial ecosystem model: Calibration and evaluation for Urochloa (syn. Brachiaria) brizantha - Fabiani Denise Bender; Santiago Vianna Cuadra; Henrique Boriolo Dias; Leandro Eduardo Annibal Silva; Monique Pires Gravina de Oliveira; Rubens Augusto Camargo Lamparelli; Osvaldo Machado Rodrigues Cabral; Sandra Furlan Nogueira; José Ricardo Macedo Pezzopane; Cristiam Bosi; Helber Custódio de Freitas; Paulo Sergio Graziano Magalhães (European Journal of Agronomy, 2024)

Understanding the Atlantic influence on climate and vegetation dynamics in western Iberia over the last 2000 years - Ricardo N. Santos; Teresa Rodrigues; Filipa Naughton; Enno Schefuß; Dulce Oliveira; João Moreno; Pedro M. Raposeiro; Graciela Gil-Romera; Alistair Morgan; Manel Leira; Sandra D. Gomes; S. Nemiah Ladd; et al. (Quaternary Science Reviews, 2024)

Insights on the regional thermal evolution from semianthracite petrology of the Fengfeng coalfield, China - Na Wang; Joan S. Esterle; Sandra Rodrigues; James C. Hower; Shifeng Dai (International Journal of Coal Geology, 2024)

Uncovering microplastics contamination in canned seafood - Diogo M. Silva; C. Marisa R. Almeida; Francisco A. Guardiola; Rúben Pereira; Sabrina M. Rodrigues; Sandra Ramos (Food Chemistry, 2024)

Preventive and therapeutic vascular photobiomodulation decreases the inflammatory markers and enhances the muscle repair process in an animal model - Tainá Caroline dos Santos Malavazzi; Lucas Andreo; Andreia Martinelli; Maria Fernanda Setúbal Destro Rodrigues; Anna Carolina Ratto Tempestini Horliana; Sandra Kalil Bussadori; Kristianne Porta Santos Fernandes; Fabio Daumas Nunes; Raquel Agnelli Mesquita-Ferrari (Journal of Photochemistry and Photobiology B: Biology, 2024)

Anaerobic Co-digestion of Expired Dairy Products and Synthetic Domestic Wastewater: Effect on Methane Potential in Batch Reactors - Danieli Fernanda Canaver Marin; Caroline Varella Rodrigues; Romário Pereira de Carvalho Júnior; Sandra Imaculada Maintinguer (BioEnergy Research, 2024)

Towards a circular bioeconomy to produce methane by co-digestion of coffee and brewery waste using a mixture of anaerobic granular sludge and cattle manure as inoculum - Caroline Varella Rodrigues; Franciele Pereira Camargo; Vitor Alves Lourenço; Isabel Kimiko Sakamoto; Sandra Imaculada Maintinguer; Edson Luiz Silva; Maria Bernadete Amâncio Varesche (Chemosphere, 2024)

Stemphylium lycopersici immobilized in mesoporous of type MCM 48 as biocatalyst for ω-transamination reactions - Maria Sandra Ramos Queiroz; Glaciela Cristina Rodrigues da Silva; Nádia Ligianara D. Nyari; Rodrigo O.M.A. de Souza; Rogério Marcos Dallago; Denise Oliveira Guimarães; Marcelo Luis Mignoni; Ivana Correa Ramos Leal (Sustainable Chemistry and Pharmacy, 2024)

Lactobacillus group and arterial hypertension: A broad review on effects and proposed mechanisms - Danilo Duarte de Assis Gadelha; José Luiz de Brito Alves; Paulo César Trindade da Costa; Mickael Sousa da Luz; Clênia de Oliveira Cavalcanti; Fabrícia França Bezerril; Juliana Franco Almeida; Josiane de Campos Cruz; Marciane Magnani; Camille Moura Balarini; Sandra Rodrigues Mascarenhas; Valdir de Andrade Braga; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Origin and nature of pores in the Toolebuc Formation, a potential unconventional target in Australia - Xiaoxiao Mao; Grant K.W. Dawson; Victor Rudolph; Sandra Rodrigues; Suzanne D. Golding (International Journal of Coal Geology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Responses of soil microbiome to copper-based materials (nano and bulk) for agricultural applications: An indoor-mesocosm experiment - Sara Peixoto; Rui G. Morgado; Marija Prodana; Diogo N. Cardoso; Catarina Malheiro; Joana Neves; Cátia Santos; Zahra Khodaparast; Maria D. Pavlaki; Sandra Rodrigues; Sónia M. Rodrigues; Isabel Henriques; et al. (NanoImpact, 2024)

Immunosuppressive effects of the mycotoxin patulin in macrophages - José Marreiro de Sales-Neto; Sandra Rodrigues-Mascarenhas (Archives of Microbiology, 2024)

New curcumin-loaded nanocapsules as a therapeutic alternative in an amnesia model - Karline da Costa Rodrigues; Manoel Rodrigues da Silva Neto; Victor dos Santos Barboza; Sandra Elisa Hass; Rodrigo de Almeida Vaucher; Janice Luehring Giongo; Ricardo Frederico Schumacher; Ethel Antunes Wilhelm; Cristiane Luchese (Metabolic Brain Disease, 2024)

Effects of amber LED on inflammatory and regulatory monocytes and lymphocytes - Kaline de Brito Sousa; Tainá Caroline dos Santos Malavazzi; Maria Fernanda Setúbal Destro Rodrigues; Tamiris Silva; Lucas Andreo; Alessandro Melo Deana; Fabio Daumas Nunes; Sandra Kalil Bussadori; Raquel Agnelli Mesquita-Ferrari; Kristianne Porta Santos Fernandes (Journal of Photochemistry and Photobiology B: Biology, 2024)

Emerging Methods for the Evaluation of Sensory Quality of Food: Technology at Service - Sandra S. Q. Rodrigues; Luís G. Dias; Alfredo Teixeira (Current Food Science and Technology Reports, 2024)
Purpose of Review Sensory evaluation holds vital significance in the food sector. Typically, humans conduct sensory analysis. Humans, being the ultimate consumers, assess food traits effectively. However, human judgment is influenced by various factors. Hence, countering subjectivity is crucial for objective evaluation while retaining hedonic insights. Recent Findings Food’s sensory assessment primarily employs humans. Various techniques differentiate, depict, or rank food. Modern sensory tools, aiming to enhance objectivity and reliability, are emerging to supplement or supplant human assessment. This advance can bolster quality, consistency, and safety by mimicking human senses such as smell, taste, and vision, mitigating risks tied to human assessors. Summary This paper provides a review about sensory analysis of food using technological methodologies. A review of different technological tools to analyze sensory characteristics of food, as well as a discussion of how those technological tools can relate to humans’ perception of food is presented.

Spatial and temporal patterns of gonadal maturation and spawning in European flounder Platichthys flesus at its southern continental edge - Vânia Freitas; Diana Santos; Diogo M. Silva; Jacinto Cunha; Sabrina M. Rodrigues; Vanessa Neves; Eduardo Rocha; Filipe Martinho; Sandra Ramos (Fisheries Research, 2024)

Optimized conditions for methane production and energy valorization through co-digestion of solid and liquid wastes from coffee and beer industries using granular sludge and cattle manure - Caroline Varella Rodrigues; Franciele Pereira Camargo; Vitor Alves Lourenço; Isabel Kimiko Sakamoto; Sandra Imaculada Maintinguer; Edson Luiz Silva; Maria Bernadete Amâncio Varesche (Journal of Environmental Chemical Engineering, 2023)

Evaluation of oxidative stress indicators as toxicity parameters after chronic exposure of Drosophila melanogaster to free curcumin and curcumin-loaded nanocapsules - Eliana Jardim Fernandes; Elize Aparecida Santos Musachio; Luana Barreto Meichtry; Dieniffer Espinosa Janner; Franciéle Romero Machado Balok; Magna Sotelo Barrientos; Nathalie Savedra Gomes; Kétnne Hanna Poleto Pinto; Mustafa Munir Mustafa Dahleh; Andrieli Rodrigues; Sandra Elisa Haas; Silvana Peterini Boeira; et al. (Food and Chemical Toxicology, 2023)

Ethylene photocatalytic degradation using TiO2 immobilized in a NETmix mili-photoreactor - Jéssica de Matos Fonseca; Sandra M. Miranda; Joana P. Monteiro; Regina de Fátima Peralta Muniz Moreira; Germán Ayala Valencia; Alcilene Rodrigues Monteiro; Vítor J.P. Vilar (Journal of Environmental Chemical Engineering, 2023)

Limosilactobacillus reuteri as sustainable biological control agent against toxigenic Fusarium verticillioides - Melissa Tiemi Hirozawa; Mario Augusto Ono; Igor Massahiro de Souza Suguiura; Sandra Garcia; Jaqueline Gozzi Bordini; Ismael Rodrigues Amador; Elisa Yoko Hirooka; Elisabete Yurie Sataque Ono (Brazilian Journal of Microbiology, 2023)

Synthetic silico-metallic particles-SSMMP-Ni and SSMMP-Ni-IL: CO2 capture and utilization - Daniela Rodrigues; Julia Wolf; Barbara Polesso; Pierre Micoud; Christophe Le Roux; Franciele Bernard; François Martin; Sandra Einloft (Fuel, 2023)

Effect of different levels of sodium in water on performance, carcass yield, and meat quality of slow-growing chickens - Débora Cristine de Oliveira Carvalho; Glayciane Costa Gois; Luan Caio Conceição da Silva; Francisco Fabricio Nunes de Souza; Mário Adriano Ávila Queiroz; Karine Vieira Antunes; Rafael Torres de Souza Rodrigues; René Geraldo Cordeiro Silva Junior; Rita de Cássia Rodrigues de Souza; Sandra Regina Freitas Pinheiro; Acácio Figueirêdo Neto (Tropical Animal Health and Production, 2023)

Before and after: A visual glimpse into the coking behaviour of coal macerals - Tara Congo; Sandra Rodrigues; Joan Esterle; Karen Steel; Silvio Maranha (Fuel, 2023)

Dietary exposure to food azo-colours in a sample of pre-school children from Southern Brazil - Constanza De Matteu Monteiro; Sila Mary Rodrigues Ferreira; Claudia Choma Bettega Almeida; Larissa Marinho Duarte; Sandra Patricia Crispim (Food Additives & Contaminants: Part A, 2023)

Embryotoxicity of silica nanoparticles in the drug delivery of domperidone in zebrafish - Lorranny Pereira de Assis Valadares; Larise Caroline Oliveira Lima; Simone Maria Teixeira de Saboia-Morais; Tatiane Moraes Arantes; Fernando Henrique Cristovan; Naiton Martins da Silva; Aline Borges Andrade; Sandra Aparecida Benite Ribeiro; Benner Geraldo Alves; Barbara do Carmo Rodrigues Virote; Ives Charlie da Silva; Mônica Rodrigues Ferreira Machado (Aquatic Toxicology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Characterisation of coal using hyperspectral core scanning systems - Sandra Rodrigues; Lionel Fonteneau; Joan Esterle (International Journal of Coal Geology, 2023)

Marine carbonate mining in the Southwestern Atlantic: current status, potential impacts, and conservation actions - Sandra Vieira Paiva; Pedro Bastos Macedo Carneiro; Tatiane Martins Garcia; Tallita Cruz Lopes Tavares; Lidriana de Souza Pinheiro; Antonio Rodrigues Ximenes Neto; Tarin Cristino Montalverne; Marcelo O. Soares (Marine Policy, 2023)

Integrated proactive drought management in hydrosystems and cities: building a nine-step participatory planning methodology - Francisco de Assis Souza Filho; Ticiana Marinho de Carvalho Studart; João Dehon Pontes Filho; Eduardo Sávio Passos Rodrigues Martins; Sérgio Rodrigues Ayrimoraes; Carlos Alberto Perdigão Pessoa; Larissa Zaira Rafael Rolim; Luiz Martins de Araujo Junior; Samiria Maria Oliveira da Silva; Taís Maria Nunes Carvalho; Sandra Helena Silva de Aquino (Natural Hazards, 2023)

Microplastic contamination in large migratory fishes collected in the open Atlantic Ocean - Rúben Pereira; Sabrina M. Rodrigues; Diogo Silva; Vânia Freitas; C. Marisa R. Almeida; Sandra Ramos (Marine Pollution Bulletin, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Reservoir lithofacies study of the Toolebuc Formation, Eromanga Basin, Australia as a potential unconventional target - Xiaoxiao Mao; Sandra Rodrigues; Joan S. Esterle; Suzanne D. Golding (International Journal of Coal Geology, 2023)

Tolerance and reduction of chromium by bacterial strains - Sandra Mara Barbosa Rocha; Marineide Rodrigues do Amorim; Mayanna Karlla Lima Costa; Tályta Carine da Silva Saraiva; Romário Martins Costa; Jadson Emanuel Lopes Antunes; Louise Melo de Souza Oliveira; Francisco de Alcantara Neto; Erika Valente de Medeiros; Arthur Prudencio de Araujo Pereira; Ademir Sergio Ferreira Araujo (Archives of Microbiology, 2022)

Patulin inhibits LPS-induced nitric oxide production by suppressing MAPKs signaling pathway - José Marreiro de Sales-Neto; Juliane Santos de França da Silva; Deyse Cristina Madruga Carvalho; Éssia de Almeida Lima; Luiz Henrique Agra Cavalcante-Silva; Aline Portantiolo Lettnin; Ana Paula de Souza Votto; Ulrich Vasconcelos; Sandra Rodrigues-Mascarenhas (Natural Product Research, 2022)

Dietary exposure to low-calorie sweeteners in a sample of Brazilian pregnant women - Larissa Marinho Duarte; Sila Mary Rodrigues Ferreira; Claudia Choma Bettega Almeida; Ana Clara da Fonseca Leitão Duran; Mariana Fagundes Grilo; Mariana de Souza Macedo; Sylvia do Carmo Castro Franceschini; Sandra Patricia Crispim (Food Additives & Contaminants: Part A, 2022)

Metabolomic Profiling of Phloem Sap from Different Pine Species and Implications on Black Capuchin - Lorena Mara A. Silva; Elenilson G. Alves Filho; Tigressa Helena S. Rodrigues; Francisca Jamila C. Louredo; Guilherme J. Zocolo; Kirley M. Canuto; Sandra B. Mikich; Dieter Liebsch; Adriana De Almeida; Edy S. De Brito (Journal of Chemical Ecology, 2022)

Lung-Brain Crosstalk in Sepsis: Protective Effect of Prophylactic Physical Exercise Against Inflammation and Oxidative Stress in Rats - Amanda Della Giustina; Judite Filgueiras Rodrigues; Erick Bagio; Sandra Bonfante; Larissa Joaquim; Graciela Zarbato; Solange Stork; Richard Simon Machado; Mariana Pereira de Souza Goldim; Lucinéia Gainski Danielski; Khiany Mathias; Carlos Dacoregio; et al. (Molecular Neurobiology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Level of genetic divergence among accessions of the native forage grass, Mesosetum chaseae Luces, for tracing strategies to conservation of germplasm collections from the brazilian pantanal - Ana Clara de Sousa Meirelles; Eliane Rodrigues Monteiro; Claudete Aparecida Mangolin; Sandra Aparecida Santos; Maria de Fátima P. S. Machado (Conservation Genetics Resources, 2022)

Aflagellar Epimastigote of Trypanosoma caninum: Biological and Ultrastructural Study of this Atypical Evolutionary Form - Kátia Cristina Silva Nascimento; Sandra Maria de Oliveira Souza; Aline Fagundes; Roger Magno Macedo Silva; Francisco Odencio Rodrigues de Oliveira Junior; Suzana Corte-Real; Juliana Helena da Silva Barros (Acta Parasitologica, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Pathogenicity of filamentous fungi towards Atta sexdens rubropilosa (Hymenoptera:﻿ ﻿Formicidae﻿) - Sandra Regina Sousa Cardoso; André Rodrigues; Luiz Carlos Forti; Nilson Satoru Nagamoto (International Journal of Tropical Insect Science, 2022)

Pyrolysis of Coconut Inflorescence Wastes: Production, Effects of Parameters, Characterization and Optimization of Phenolic-Rich Bio-Oil - Rodrigo Oliveira Farias; Pollyanna Vanessa Santos Lins; Rafaela Gabriel; Alson David Rodrigues Silva; Lívia Luísa Melo Carvalho; Lucas Meili; Allan Almeida Albuquerque; Sandra Helena Vieira Carvalho; João Inácio Soletti; Mozart Daltro Bispo (International Journal of Environmental Research, 2022)

Ouabain inhibits p38 activation in mice neutrophils - Luiz Henrique Agra Cavalcante‑Silva; Deyse Cristina Madruga Carvalho; Éssia de Almeida Lima; Sandra Rodrigues‑Mascarenhas (Inflammopharmacology, 2021)

Dynamics of bacterial and archaeal communities along the composting of tannery sludge - Ademir Sergio Ferreira Araujo; Arthur Prudêncio de Araujo de Pereira; Jadson Emanuel Lopes Antunes; Louise Melo de Souza Oliveira; Wanderley José de Melo; Sandra Mara Barbosa Rocha; Marineide Rodrigues do Amorim; Fabio Fernando Araujo; Vania Maria Maciel Melo; Lucas William Mendes (Environmental Science and Pollution Research, 2021)

Grazer-Induced Chemical Defense in a Microcystin-Producing Microcystis aeruginosa (Cyanobacteria) Exposed to Daphnia gessneri Infochemicals - Mauro Cesar Palmeira Vilar; Thiago Ferreira da Costa Pena Rodrigues; Aloysio da Silva Ferrão-Filho; Sandra Maria Feliciano de Oliveira e Azevedo (Journal of Chemical Ecology, 2021)

Plant growth-promoting bacteria improve growth and nitrogen metabolism in maize and sorghum - João Pedro Alves Aquino; Jadson Emanuel Lopes Antunes; Aurenívia Bonifácio; Sandra Mara Barbosa Rocha; Marineide Rodrigues Amorim; Francisco Alcântara Neto; Ademir Sérgio Ferreira Araujo (Theoretical and Experimental Plant Physiology, 2021)

Metalaxyl-M, phosphorous acid and potassium silicate applied as soil drenches show different chestnut seedling performance and protection against Phytophthora root rot - Jorge Nuno Rosário; Valentim Coelho; M. Ângelo Rodrigues; Soraia Raimundo; Sandra Afonso; Margarida Arrobas; M. Eugénia Gouveia (European Journal of Plant Pathology, 2021)

Cultivation Practices of Sugarcane: An Analysis of the Competitiveness of Sugarcane Suppliers in Brazil - Fernando Rodrigues de Amorim; Timóteo Ramos Queiroz; Sandra Cristina de Oliveira; Wagner Luiz Lourenzani (Sugar Tech, 2021)

Influence of Iron on Physiological Parameters and Intracellular Microcystin in Microcystis Panniformis Strain Isolated from a Reservoir in the Amazon - Elisabete Lourdes do Nascimento; Priscila Rodrigues Koschek; Maria Elisângela Venâncio dos Santos; Ana Beatriz Furlanetto Pacheco; Andreia Maria da Anunciação Gomes; Cristina Maria Magalhães de Souza; Wanderley Rodrigues Bastos; Sandra Maria Feliciano de Oliveira Azevedo (Current Microbiology, 2021)

Emission inventory for harbour-related activities: comparison of two distinct bottom-up methodologies - Sandra Sorte; Vera Rodrigues; Rúben Lourenço; Carlos Borrego; Alexandra Monteiro (Air Quality, Atmosphere & Health, 2021)

A controlled-release fertilizer improved soil fertility but not olive tree performance - Ermelinda Silva; Margarida Arrobas; Alexandre Gonçalves; Sandra Martins; Soraia Raimundo; Luis Pinto; Cátia Brito; José Moutinho-Pereira; Carlos M. Correia; M. Ângelo Rodrigues (Nutrient Cycling in Agroecosystems, 2021)

Food intake in early life and epigenetic modifications of pro-opiomelanocortin expression in arcuate nucleus - Sandra Aparecida Benite-Ribeiro; Valkíria Alves de Lima Rodrigues; Mônica Rodrigues Ferreira Machado (Molecular Biology Reports, 2021)

5-Aza-2’-deoxycytidine induces a greater inflammatory change, at the molecular levels, in normoxic than hypoxic tumor microenvironment - Ísis Salviano Soares de Amorim; Juliana Alves Rodrigues; Pedro Nicolau; Sandra König; Carolina Panis; Adenilson de Souza da Fonseca; Andre Luiz Mencalha (Molecular Biology Reports, 2021)

Association between exposure to air pollution during intrauterine life and cephalic circumference of the newborn - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R. D. M. Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Environmental Science and Pollution Research, 2021)

Topical application of (S)-(–)-limonene is as effective as phonophoresis for improving oxidative parameters of injured skeletal muscle in rats - Marta Maria Barbosa Santos; Luís Fernando Sousa Filho; Jéssica Batista De Souza; José Evaldo Rodrigues De Menezes Filho; Thássio Ricardo Ribeiro Mesquita; Michel Santana Santos; Carla Maria Lins De Vasconcelos; Sandra Lauton-Santos; Evaleide Diniz De Oliveira (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Soil and Plant Analyses to Diagnose Hop Fields Irregular Growth - Sandra Afonso; Margarida Arrobas; M. Ângelo Rodrigues (Journal of Soil Science and Plant Nutrition, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Association between maternal exposure to air pollution before conception and sex determination in the city of São Paulo - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R D M Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Air Quality, Atmosphere & Health, 2020)

Morpho-Anatomical and Molecular Characterization of the Oversprouting Symptoms Caused by Fusarium decemcellulare in Guarana Plants (Paullinia cupana var. sorbilis) - Claudia Afras de Queiroz; Kedma da Silva Matos; Igor Kelvyn Cavalcante Lobo; Sandra Barbosa de Sousa; Celli Rodrigues Muniz; Michel E. Beleza Yamagishi; Guilherme Julião Zocolo; Rogério Eiji Hanada; Luadir Gasparotto; Nelcimar Reis Sousa; Edmar Vaz de Andrade; Isabelle Bezerra Cordeiro; et al. (Tropical Plant Biology, 2020)

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Ouabain reduces the expression of the adhesion molecule CD18 in neutrophils - Luiz Henrique Agra Cavalcante-Silva; Éssia de Almeida Lima; Deyse C. M. Carvalho; Sandra Rodrigues-Mascarenhas (Inflammopharmacology, 2020)

Bradyrhizobium sp. enhance ureide metabolism increasing peanuts yield - Thais Grassi Gericó; Renan Francisco Rimoldi Tavanti; Sandra Cristina de Oliveira; Ana Elisa Bressan Smith Lourenzani; Jéssica Pacheco de Lima; Rodolfo Pires Ribeiro; Leandro Cesar Cusim dos Santos; André Rodrigues dos Reis (Archives of Microbiology, 2020)

The effect of different grazing heights on carcass and meat quality characteristics of Nellore cattle fattened in pastures of Convert grass - Thiago Trento Biserra; Ulysses Cecato; Sandra Galbeiro; Ana Maria Bridi; Henrique Jorge Fernandes; Camila Fernandes Domingues Duarte; Diogo Rodrigues Da Silva; João Vitor Rosa Vicente; Camila Piechnicki Rogel (Tropical Animal Health and Production, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Giardia spp. and Cryptosporidium spp. removal efficiency of a combined fixed-film system treating domestic wastewater receiving hospital effluent - Sandra Yamashiro; Mário Luiz Rodrigues Foco; Carolina Ortiz Pineda; Juliana José; Edson Aparecido Abdul Nour; Isabel Cristina Vidal Siqueira-Castro; Regina Maura Bueno Franco (Environmental Science and Pollution Research, 2019)

Technological advancements for the development of stem cell-based models for hepatotoxicity testing - Alessandra Natale; Koen Vanmol; Aysu Arslan; Sandra Van Vlierberghe; Peter Dubruel; Jürgen Van Erps; Hugo Thienpont; Matij Buzgo; Joost Boeckmans; Joery De Kock; Tamara Vanhaecke; Vera Rogiers; et al. (Archives of Toxicology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Influence of different complexity levels of road traffic models on air quality modelling at street scale - Bruno Vicente; Sandra Rafael; Vera Rodrigues; Hélder Relvas; Mariana Vilaça; João Teixeira; Jorge Bandeira; Margarida Coelho; Carlos Borrego (Air Quality, Atmosphere & Health, 2018)

Biomonitoring birds: the use of a micronuclei test as a tool to assess environmental pollutants on coffee farms in southeast Brazil - Henrique Nazareth Souto; Edimar Olegário de Campos Júnior; Carlos Fernando Campos; Tamiris Sabrina Rodrigues; Boscolli Barbosa Pereira; Sandra Morelli (Environmental Science and Pollution Research, 2018)

Numerical and physical assessment of control measures to mitigate fugitive dust emissions from harbor activities - Sandra Sorte; Vera Rodrigues; Ana Ascenso; Sylvio Freitas; Joana Valente; Alexandra Monteiro; Carlos Borrego (Air Quality, Atmosphere & Health, 2018)

Kinetic and thermodynamic parameters, and partial characterization of the crude extract of tannase produced by Saccharomyces cerevisiae CCMB 520 - Lúzia Morgana de Melo Lopes; Larissa Hayannyelly Costa Batista; Marcos Juliano Gouveia; Tonny Cley Campos Leite; Marcelo Rodrigues Figueira de Mello; Sandra Aparecida de Assis; Amanda Reges de Sena (Natural Product Research, 2018)

Author Correction: Ouabain attenuates ovalbumin-induced airway inflammation - José Guilherme F. M. Galvão; Luiz Henrique Agra Cavalcante-Silva; Deyse Cristina M. Carvalho; Laércia Karla D. P. Ferreira; Talissa Mozzini Monteiro; Adriano Francisco Alves; Larissa Adiles M. P. Ferreira; Francisco Allysson A. F. Gadelha; Marcia Regina Piuvezam; Sandra Rodrigues-Mascarenhas (Inflammation Research, 2018)

Ouabain attenuates ovalbumin-induced airway inflammation - José Guilherme F. M. Galvão; Luiz Henrique Agra Cavalcante-Silva; Deyse Cristina M. Carvalho; Laércia Karla D. P. Ferreira; Talissa Mozzini Monteiro; Adriano Francisco Alves; Larissa Adilis M. P. Ferreira; Francisco Allysson A. F. Gadelha; Marcia Regina Piuvezam; Sandra Rodrigues-Mascarenhas (Inflammation Research, 2017)

The carboxylic acid transporters Jen1 and Jen2 affect the architecture and fluconazole susceptibility of Candida albicans biofilm in the presence of lactate - Rosana Alves; Sandra Mota; Sónia Silva; Célia F. Rodrigues; Alistair J. P. Brown; Mariana Henriques; Margarida Casal; Sandra Paiva (Biofouling, 2017)

Spittlebugs (Hemiptera: Cercopidae) and their host plants: a strategy for pasture diversification - R. Alvarenga; Alexander M. Auad; Jair C. Moraes; Sandra E. B. Silva; Brunno S. Rodrigues; Giani B. Silva (Applied Entomology and Zoology, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase - Caio Rodrigues-Silva; Sandra M. Miranda; Filipe V. S. Lopes; Mário Silva; Márcia Dezotti; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar; Eugénia Pinto (Environmental Science and Pollution Research, 2017)

Semi-autonomous inline water analyzer: design of a common light detector for bacterial, phage, and immunological biosensors - Elodie C.T. Descamps; Damien Meunier; Catherine Brutesco; Sandra Prévéral; Nathalie Franche; Ingrid Bazin; Bertrand Miclot; Philippe Larosa; Camille Escoffier; Jean-Raphael Fantino; Daniel Garcia; Mireille Ansaldi; et al. (Environmental Science and Pollution Research, 2017)

Bacterial host and reporter gene optimization for genetically encoded whole cell biosensors - Catherine Brutesco; Sandra Prévéral; Camille Escoffier; Elodie C. T. Descamps; Elsa Prudent; Julien Cayron; Louis Dumas; Manon Ricquebourg; Géraldine Adryanczyk-Perrier; Arjan de Groot; Daniel Garcia; Agnès Rodrigue; et al. (Environmental Science and Pollution Research, 2017)

Filamentous Fungi Isolates of Contaminated Sediment in the Amazon Region with the Potential for Benzo(a)pyrene Degradation - Hilton Marcelo de Lima Souza; Lara Durães Sette; Adolfo José da Mota; Joaquim Ferreira do Nascimento Neto; André Rodrigues; Tássio Brito de Oliveira; Fernando Mendes de Oliveira; Luiz Antônio de Oliveira; Hileia dos Santos Barroso; Sandra Patricia Zanotto (Water, Air, & Soil Pollution, 2016)

Hyaluronidase decreases neutrophils infiltration to the inflammatory site - Marcio Fronza; Cornélia Muhr; Denise Sayuri Calheiros da Silveira; Carlos Artério Sorgi; Stephen Fernandes de Paula Rodrigues; Sandra Helena Poliselli Farsky; Francisco Wanderley Garcia Paula-Silva; Irmgard Merfort; Lúcia Helena Faccioli (Inflammation Research, 2016)

Comparison of UV photolysis, nanofiltration, and their combination to remove hormones from a drinking water source and reduce endocrine disrupting activity - Sandra Sanches; Alexandre Rodrigues; Vitor V. Cardoso; Maria J. Benoliel; João G. Crespo; Vanessa J. Pereira (Environmental Science and Pollution Research, 2016)

Mercurial exposure of residents of Santarém and Oriximiná cities (Pará, Brazil) through fish consumption - Jean-Paul Bourdineaud; Gilles Durrieu; Sandra Layse Ferreira Sarrazin; Wânia Cristina Rodrigues da Silva; Rosa Helena Veras Mourão; Ricardo Bezerra de Oliveira (Environmental Science and Pollution Research, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Differential Effects of Fluoride During Osteoblasts Mineralization in C57BL/6J and C3H/HeJ Inbred Strains of Mice - Sandra S. Matsuda; Thelma L. Silva; Marília A. Buzalaf; Antonio C Rodrigues; Rodrigo Cardoso de Oliveira (Biological Trace Element Research, 2014)

Carcass and non-carcass component yields of crossbred Boer and Brazilian semiarid indigenous goats subjected to different feeding levels - Samara Rodrigues Martins; Mario Luiz Chizzotti; Sandra Mari Yamamoto; Rafael Torres de Souza Rodrigues; Karina Costa Busato; Tiago Santos Silva (Tropical Animal Health and Production, 2014)

Sporothrix schenckii sensu stricto Isolated from Soil in an Armadillo’s Burrow - Anderson Messias Rodrigues; Eduardo Bagagli; Zoilo Pires de Camargo; Sandra de Moraes Gimenes Bosco (Mycopathologia, 2014)

Berlengas Biosphere Reserve - Plan for the assessment of ecosystem services and functions - Leandro Sergio; Marques Daniel; Mouga Teresa; Coelho Helena; Rodrigues Sandra; Maranhão Paulo (Frontiers in Marine Science, 2014)

Phylogeography and genetic diversity of the Robin (Erithacus rubecula) in the Azores Islands: Evidence of a recent colonisation - Pedro Rodrigues; Ricardo Jorge Lopes; Sergei V. Drovetski; Sandra Reis; Jaime A. Ramos; Regina Tristão da Cunha (Journal of Ornithology, 2013)

Epistatic interaction of Arg72Pro TP53 and −710 C/T VEGFR1 polymorphisms in breast cancer: predisposition and survival - Patricia Rodrigues; Jessica Furriol; Eduardo Tormo; Sandra Ballester; Ana Lluch; Pilar Eroles (Molecular and Cellular Biochemistry, 2013)

Paracoccidioidomycosis in a Dog: Case Report of Generalized Lymphadenomegaly - Marconi Rodrigues de Farias; Larissa Anuska Zeni Condas; Márcio Garcia Ribeiro; Sandra de Moraes Gimenes Bosco; Marisol Dominguez Muro; Juliana Werner; Raquel Cordeiro Theodoro; Eduardo Bagagli; Sílvio Alencar Marques; Marcello Franco (Mycopathologia, 2011)

Haplotypes of the bovine IgG2 heavy gamma chain in tick-resistant and tick-susceptible breeds of cattle - Wanessa Araújo Carvalho; Patricia Ianella; Frederico G. C. Arnoldi; Alexandre Rodrigues Caetano; Sandra Regina Maruyama; Beatriz Rossetti Ferreira; Luís Henrique Andreucci Conti; Marcia Ramos Monteiro da Silva; José Otavio F. Paula; Antonio Augusto Mendes Maia; Isabel K. Ferreira de Miranda Santos (Immunogenetics, 2011)

Molecular characterization of a miraculin-like gene differentially expressed during coffee development and coffee leaf miner infestation - Jorge Maurício Costa Mondego; Melina Pasini Duarte; Eduardo Kiyota; Leandro Martínez; Sandra Rodrigues de Camargo; Fernanda P. De Caroli; Beatriz Santos Capela Alves; Sandra Maria Carmello Guerreiro; Maria Luiza Vilela Oliva; Oliveiro Guerreiro-Filho; Marcelo Menossi (Planta, 2011)

Contamination Levels and Preliminary Assessment of the Technical Feasibility of Employing Natural Attenuation in 5 Priority Areas of Presidente Bernardes Refinery in Cubatão, São Paulo, Brazil - René P. Schneider; Sandra C. Morano; Maria Alejandra C. Gigena; Silvia K. Missawa; Rafael C. S. Rocha; Lucimara Rodrigues Da Silva; Nelson Ellert; Sérgio Kataoka; Carlos Katsuragi; Carlos Da Silva Rosa; Luiz Calixto De Oliveira Filho (Environmental Monitoring and Assessment, 2006)

GENEHUNTER versus SimWalk2 in the context of an extended kindred and a qualitative trait locus - Sandra Romero-Hidalgo; Eliane R. Rodrigues; Eduardo Gutirrez-Pea; Laura Riba; Mara Teresa Tusi-Luna (Genetica, 2005)